FOREIGN LANGUAGE SPEAKING ANXIETY: A CASE STUDY AT ENGLISH DEPARTMENT STUDENTS OF IAIN LHOKSEUMAWE AND AL MUSLIM UNIVERSITY - Fitriah Fitriah; Hayatul Muna (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
Language anxiety becomes an important area on language teaching and learning. It has been a common issue in the EFL context and had a profound consequence in language teaching. Furthermore, a feeling of anxiety has been experienced by a number of foreign language learners in their English language classroom. Therefore, the objective of this research was to investigate some factors influenced the students’ anxiety and also to find out kinds of anxiety experienced by them. The data were collected through FLCAS (Foreign language Classroom Anxiety Scale) from 30 English Department students of IAIN Lhokseumawe and 25 students of Al Muslim University and semi-structured interviews with 6 students as research’s participant. The data were analyzed descriptively to answer research questions. The findings indicated that students of IAIN Lhokseumawe had a higher level of anxiety compared with students of Al Muslim University. In addition, some factors causing students’ anxiety were lack of mental readiness, knowledge of vocabulary, pronunciation, grammar and prior knowledge of the classroom activities, including the anxiety to take Anxiety Test.